ADVANTAGES OF TEACHING FOREIGN LANGUAGES IN HIGHER EDUCATION - Mengniyozova Gulnora Toshtemirovna (Western European Studies, 2025)
This article explores the advantages of teaching foreign languages in higher education institutions. It highlights how learning foreign languages enhances students’ cognitive skills, intercultural competence, and professional opportunities. The study also examines the role of foreign language education in fostering critical thinking, global awareness, and communication abilities among students. Special attention is given to practical methods and strategies for effective language teaching, as well as the benefits for students’ personal and academic development.
Keywords: Foreign languages; higher education; language teaching